Contribution to Lateral Torsional Buckling of Girders with Rotational Restraints. Issue 4 (14th September 2022) - Müller, Andreas; Taras, Andreas
Abstract: The instability case of lateral torsional buckling (LTB) under bending load My is known to be of decisive importance in the design of beams with open cross‐sections. This instability case is expressed by a lateral displacement and simultaneous torsion (or twisting) of the member axis. The restraint of one or both of these deformation components represents an effective and practice oriented method to stabilize beams against LTB. In practice, therefore, use is made of regulations from the current version of EN 1993‐1‐1:2010, Annex BB, which allow for the consideration of the stabilizing effect of continuous and planar components directly connected to the compression chords of the beams. This paper presents the results of a study that investigated the effects of the innovations introduced in the draft standard for the 2nd generation of EN 1993‐1‐1 for the LTB verification of beams with I and H cross‐sections on the regulations for the calculation of the minimum stiffness of a rotational restraint to avoid LTB. In the first part of the paper, the background of the existing and new regulations is discussed together with previous proposals for adapting the definition of the minimum rotation restraint. In addition, a comparison is made with current specifications for the minimum rotational stiffness contained in the National Annex of DIN EN 1993‐1‐1. Subsequently, the regulations of the minimum rotational stiffness in prEN1993‐1‐1, Annex D are assessed.